Propionate, rather than acetate or butyrate, ameliorates methamphetamine-induced hepatotoxicity and enterotoxicity in mice by downregulating the TLR4/NF-κB pathway - Li-Jian Chen; Xiu-Wen Li; Yi Liu; Jia-Li Liu; Jian-Zheng Yang; Jia-Hao Li; Clare Hsu; Long Chen; Jia-Hao Zeng; Xiao-Li Xie; Qi Wang (Journal of Functional Foods, 2023)
The abuse of methamphetamine (METH) has emerged as a major public health concern, causing liver and intestinal damage upon exposure. Short chain fatty acids (SCFAs) produced by dietary fiber, including acetate, propionate, and butyrate, have been reported to alleviate various liver toxicities and exhibit distinct physiological effects. However, the role of SCFAs in mitigating METH-induced liver and intestinal damage remains unexplored. This study is designed to elucidate this potential therapeutic effect, by administering either METH or saline via injection to BALB/c mice, supplemented with acetate, propionate, or butyrate in their drinking water. We discovered that propionate demonstrated the most significant effect in mitigating pathological changes, glycogen storage, inflammation, and hepatic function impairments in the liver induced by METH. Propionate supplementation attenuated damage to the intestinal epithelial barrier, restored mucus-secreting cells, inhibited intestinal inflammation, suppressed intestinal hyperpermeability, and reduced lipopolysaccharide (LPS) leakage caused by METH. With the alleviation of LPS endotoxemia, the TLR4/MyD88/NF-κB pathway associated with inflammation in the liver and colon was inhibited. In conclusion, propionate supplementation ameliorated hepatic and colon dysfunction and inflammation resulting from METH exposure through suppression of the TLR4/MyD88/NF-κB pathway.